Urinary cadmium levels in active and retired coal miners. Issue 7 (18th April 2017) - Isermann, Julia; Prager, Hans-Martin; Ebbinghaus, Rainer; Janasik, Beata; Wasowicz, Wojciech; Dufaux, Bertinus; Meyer, Hans-Friedrich; Widera, Agata; Selinski, Silvia; Hengstler, Jan G.; Golka, Klaus
ABSTRACT: A meta-analysis, based upon 24 publications, showed a significantly elevated risk for urinary bladder cancer amongst miners. In European underground hard coal mining areas, an increased risk for urinary bladder cancer development was noted among hard coal miners, in particular in three investigations in the greater Dortmund area. However, the cause remains unclear. As cadmium (Cd), which was reported to be a bladder carcinogen in humans and is a constituent of coal, the aim of this study was to determine urinary Cd levels in active and retired hard coal miners and assess whether hard coal miners demonstrated elevated metal levels. In total, 103 retired and 25 active hard coal miners as well as 18 controls without any history of hard coal mining were investigated for urinary Cd levels. Urinary Cd concentrations, in addition to other elements, were analyzed in spot urines by ICP-MS-based multi-element analysis in a Department for Forensic and Clinical Toxicology. Limit of detection (LOD) for Cd was 0.5 μg/L. Reference value for occupationally non-exposed working age population was 0.8 μg/L. In total, 49% of all underground coal miners were exposed to coal dust, 12% to grinded rock, and 39% to both. Urinary Cd levels in retired as well as active coal miners and controls were clearly below the Biological Exposure Index. Urinary Cd concentration is a suitable biomarker to evaluate the metallic load of the body, as the half-life is > than 10 years. The detected urinary Cd levels in retired and active coal miners indicated underground hard coal miners were not apparently exposed to Cd to a occupationally-relevant concentration.